Size and profitability in cooperative banking - Lagoa, S. (2014)
The European cooperative banking plays an important role in promoting savings and in financing small and medium enterprises. Its distinctive characteristics have allowed it to go by the Subprime crisis with a remarkable resilience. Nevertheless, cooperative banks are inserted in a very competitive market, where they suffer a constant pressure to improve competitive position. One strategy often followed to deal with that pressure is to increase the size of local cooperative banks. Based on the data of a Portuguese cooperative banking group for 2009-11, in this paper we assess the impact of size on aggregate assets profitability, making also a disaggregated analysis of the ratios affecting aggregate profitability. After controlling for the idiosyncratic characteristics of local banks, size has a positive effect on assets return. But this effect disappears after controlling for credit risk, suggesting that the effect of size works through better credit risk management.